Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

2(m+1)-n^3;m=-2, n=3. cluless!!! please help!!! 

Sagot :

You need to plug in the values of m and n to work this problem. The problem would look like the foolwing:
2(-2 + 1) - 3^3
2(-1) - 3 * 3 * 3
-2 - 27
-29
[tex]Put\ values\ of\ m=-2;\ n=3\ in\ expression\ 2(m+1)-n^3:\\\\2(-2+1)-3^3\\\\Use\ PEMDAS:\\\\2(-1)-27=-2-27=-29[/tex]